SPIRITUALITAS DAN KULTUR - Marpaung, Manangar C. (UNIKA Santo Thomas, 2008)
It is nowadays more realized that faith has not to be put in contrast with cultures. The spirituality of incarnated Logos, increasingly developed today, has opened the eyes of believers to observe that praxis of faith must enter into many kinds of cultures in particular historical places and time. Spirituality dan cultures are reciprocal, not polarized each other. Both are coherent, not two poles pushing each other. The reciprocity between spirituality and cultures is the effect of faith entering into cultures, and it is no other than the effect of incarnated Logos. Spirituality entering into cultures makes cultures spiritualized, and vice versa, spirituality culturalized.